Regulation and Dysfunction of Apoptosis - Tutar, Yusuf (IntechOpen, 2022)
The book provides a comprehensive review of apoptotic cell death. It discusses the mechanism of apoptosis and emerging principles of drug resistance in cancer. The development of novel drug targets and drug delivery systems for inhibiting or inducing apoptosis are the ultimate goal. Further, upregulation of anti-apoptotic proteins and loss of pro-apoptotic proteins strongly favors apoptosis evasion. The ability of cancer cells to evade apoptosis is critical for the progression and clonal expansion of malignantly transformed cells. Defective apoptosis imparts proliferative advantage to cancer cells or cells with the potential to become cancerous. The mechanisms employed by cancer cells to evade apoptosis can be used in the strategic design of therapeutic regimens aimed at exploiting apoptotic signaling networks to ensure tumor-specific cell death. This book presents knowledge of the molecular mechanisms of defective apoptosis that could be translated into the development of novel therapeutic agents and therapeutic modalities for cancer treatment.